2022
DOI: 10.1109/access.2022.3192452
|View full text |Cite
|
Sign up to set email alerts
|

Human Activity Recognition Based on Multichannel Convolutional Neural Network With Data Augmentation

Abstract: In view of the excellent portability and privacy protection of wearable sensor devices, human activity recognition (HAR) of wearable devices has increased applications in human-computer interaction, health care, etc. Therefore, it is necessary to recognize various human activities accurately and efficiently. In this paper, we propose a multi-channel convolutional neural network with data augmentation for HAR, denoted AMC-CNN. First, the sliding windows in time series are used to construct the feature window, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…In the former, both ML techniques and CNNs, DL methods, are commonly employed, while the latter predominantly relies on thresholding and machine learning methods. Furthermore, when examining studies related to HAR based on vibration-based approaches, it is observed that CNN techniques are extensively utilized in these studies as well [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the former, both ML techniques and CNNs, DL methods, are commonly employed, while the latter predominantly relies on thresholding and machine learning methods. Furthermore, when examining studies related to HAR based on vibration-based approaches, it is observed that CNN techniques are extensively utilized in these studies as well [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…A unique shallow CNN with a C3 block was suggested for sensor-based HAR, where all channels in the same layer have extensive interaction to capture distinctive features in raw sensor data [50]. An augmented multichannel convolutional neural network (AMC-CNN) model was proposed to better explore feature patterns in time series and enhance the capability of HAR [51]. To improve the accuracy of human activity recognition (HAR), a novel approach called convolution ternary (HAR-CT) was proposed, which enhances a CNN using the trained ternary quantization (TTQ) approach [52].…”
Section: Literature Reviewmentioning
confidence: 99%